Trust, mental models and community participation in transition: Evidence from rural Ukraine. Issue 2 (June 2019) - Kvartiuk, Vasyl
Abstract: As participatory governance approaches find their way into the development agendas in transition countries, a key question is how to increase citizens' participation rates. This study examines how social trust and mental models inherited from the communist past shape individual decisions to participate in rural collective action. Using unique data from rural Ukraine, I approach these questions empirically distinguishing different types of participation. I find that social trust and mental models about the roles of communities and the state stemming from the Soviet past affect participation with some reservations. Results suggest that community-driven initiatives should invest more in educational and awareness-raising activities.